Pengaruh Iklan Dan Harga Terhadap Keputusan Pembelian Keramik Pada Depo Jaya Bangunan Kota Mataram - Dwiyaldi, Neza Azra (Postgraduate, University of Mataram, 2024)
This study aims to determine the effect of Advertising and Price on Purchase Decisions at the Depo Jaya Bangunan in Mataram City. The population in this study were all Depo Jaya Bangunan consumers in the city of Mataram, while the sample of this study was 100 Depo Jaya Bangunan consumers using a probability sampling technique. This type is associative research. This data processing uses SPSS, where validity test, reliability test, classical assumption test, multiple linear regression test, t test and coefficient of determination (R2) test are carried out. Results Based on the analysis test, all variables have a partial effect where Advertising has a positive effect on Purchase Decisions, Price has a significant effect on Purchase Decisions. Based on these results, it is recommended that Depo Jaya Bangunan can reproduce advertising and also continue stabilize prices so that it can make consumers continue to make purchases at Depo Jaya Bangunan